Strategi Public Relations Yayasan Darut Tauhid Bandung dalam Membangun Branding di Akun Instagram @wakafdt sebagai Lembaga Penghimpun Wakaf. - Ashari, Dias; Arifin, Bustanul (LPPM Universitas HKBP Nommensen, 2024)
In creating branding in the era 5.0 can be analogous as two sides of the currency, on the one hand there are different opportunities and references but on the other side there are also challenges because the internet media is accessed by different groups that must have their own needs. In responding to these challenges, the role of public relations in shaping, creating andining a good image must be very much needed by an agency. In line with the research that will be carried out against the Tauhid Darut Foundation in Bandung City. The research is aimed at analyzing the public relations strategy designed by the Darut Tauhid Foundation in designing branding on social media Instagram. As for the research method used in this research is qualitative with data analysis techniques descriptively. In this study there are findings based on data-result analysis from instagram account @wakafdt by applying Philip Kotler theory related to seven main elements namely PENCILS in using public relations strategy. The results and conclusions of this research show that the Foundation of Darut Tauhid Bandung has established branding as a foundation that cares about the goods of the people, one of them as a collective agency of wakaf through publication, exhibitions, news, relations with the community, relationships with the media, conducting approaches and organizing cooperation and participating in humanitarian activities. It is expected that this research could have implications either theoretically or methodologically for academics or future researchers.